Thyroid Dysfunction in Individuals with Type 2 Diabetes Mellitus and Its Relationship with Diabetic Nephropathy: A Hospital Based Cross-Sectional Study - Shrewastwa, Mukesh Kumar; Mahat, Arun Kumar; BK, Shyam Kumar; Sah, Bishesh; Karn, Subhash Lal (Journal of Nepalgunj Medical College, 2025)
Introduction: People diagnosed with type 2 diabetes mellitus have a heightened susceptibility to thyroid-related issues. For these individuals, hypothyroidism can exacerbate microvascular complications like diabetic nephropathy, and the combination of diabetes and hypothyroidism significantly elevates the risk of cardiovascular problems. Conducting screenings for thyroid dysfunction in type 2 diabetic patients allows for the early identification and management of hypothyroidism. Aims: To evaluate how common thyroid dysfunction is among those with type 2 diabetes and to explore the possible relationship between thyroid issues and complications associated with diabetes like diabetic nephropathy. Methods: This study was a cross-sectional analysis conducted at the Department of biochemistry with collaboration to medicine of Nepalgunj medical college & teaching hospital, kohalpur, from June 2024 to May 2025. It included 400 outpatients with type 2 diabetes mellitus who had no previous history of thyroid disorders, chronic liver disease, or acute illnesses. All participants were evaluated for diabetic complications, such as nephropathy. Furthermore, thyroid function tests were performed on all participants using the chemiluminescence immunoassay technique. Results: The prevalence of thyroid dysfunction among individuals with type 2 diabetes mellitus was identified to be 34.5%. Hypothyroidism was identified in 28% of the participants, whereas 6.5% were diagnosed with hyperthyroidism. The occurrence of thyroid dysfunction was notably higher in women compared to men. Additionally, a significant relationship was established between thyroid dysfunction and diabetic complications, specifically nephropathy, within the study group (P<0.05). Conclusion: There is a statistically significant relationship between thyroid dysfunction and diabetic nephropathy, indicating that individuals with diabetes who also have thyroid dysfunction are at a higher risk of developing nephropathy.